2020
DOI: 10.1007/s11764-020-00883-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and nutrition interventions for older adults with cancer: a systematic review

Abstract: The aim of this review was to summarize the current literature for the effectiveness of activity and nutritional based interventions on health-related quality of life (HRQoL) in older adults living with and beyond cancer (LWBC). Methods We conducted systematic structured searches of CINAHL, Embase, Medline, Cochrane CENTRAL databases, and bibliographic review. Two independent researchers selected against inclusion criteria: (1) lifestyle nutrition and/or activity intervention for people with any cancer diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 78 publications
(346 reference statements)
1
41
1
Order By: Relevance
“…Current PA studies target predominantly older breast and prostate cancer survivors, which limits the reproducibility of the evidence in other types of cancer such as haematological malignancies. 15 24 44 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current PA studies target predominantly older breast and prostate cancer survivors, which limits the reproducibility of the evidence in other types of cancer such as haematological malignancies. 15 24 44 …”
Section: Discussionmentioning
confidence: 99%
“…The OCAPI trial was based on strategies, mainly derived from behavioural change theories, 45 such as providing social support from the certified exercise instructor, that were found to be effective to improved PA in older adults with or without cancer. 15 24 25 44 46 47 These strategies will be evaluated by patients from the OCAPI study, at the end of the intervention with a semi-structured questionnaire, to select the most relevant ones for future implementation on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bioactive compounds in diet may directly affect both LGI and tumorigenesis [233][234][235]. However, according to a recent review, most of the studies on PA interventions in cancer patients do not properly consider nutritional aspects [236].…”
Section: Effects Of Physical Activity On Adipose Tissue Low-grade Inflammation and Tumor Progressionmentioning
confidence: 99%
“…Similarly, in a recently published systematic review focusing on effects of nutrition and physical activity interventions among older patients with cancer, the researchers had to lower their initial age cut-off criterion from ≥70 to ≥60 years of age, as they did not find any studies in the initial search. Even with a cut-off of ≥60 years and with inclusion of all treatments (and non-treatment) only a small number of studies were identified [ 17 ].…”
Section: Introductionmentioning
confidence: 99%